A Cross Sectional Study “Impact of Corona Virus Pandemic on Nursing Education: A Paradigm Shifting or Sustaining the Roots? - Mahendra Kumar Saini; Shelly; Binal Joshi; Ankita Singh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background:COVID 19 outbreak miens critical concern to global education system across the world.The closure of universities has left billions of students behind. Nursing educators and students relied ontechnology to continue learning online during the pandemic. However, online education is hampered by thelack of networks, power, infrastructure such as inaccessible and lack of digital skills.Aim: The aim of the study was to evaluate the impact of the COVID 19 outbreak on nursing education.Objectives:1. To assess the perception regarding impact of corona pandemic on nursing education, limitations ofE-learning and required modifications among nursing educators.2. To find out the association between perception of nursing educators with their socio-demographicvariables.Material and Methods: Quantitative Cross sectional research design was adopted with Non probabilitytechnique(Convenient sampling) .Data were collected through a Google form consisting of selfstructured Likert scale on perceptions of nursing educators. The Subdomains of the perception were impactof COVID-19 outbreak on Nursing education, Limitations of e-learning and essential modifications required.Result: of the study revealed that the corona pandemic outbreak has adversely impacted nursing educationand urgent need to implement effective e-learning teaching learning strategies of nursing educators tounderstand their perception and issues they are facing during e- classes to foster teaching-learning.Themean and SD of (7.9 + 3.9) shows negative impact of COVID pandemic on nursing education and are oflimitations in E-learning methods with a mean and SD score of (6.2 + 2.4).Conclusion: The process of imparting education has seen a sea change during the threat of the COVIDpandemic. Besides, technology is affecting every side of society and changing it regularly. Challenges inthe E-learning context shows the requirement for up-gradation in institutional technology infrastructure andteacher’s capacity building training to improve technological expertise.